Continuing Professional Development (CPD) of Senior High School Teachers of English - Hotna Sari Siregar; Soni Mirizon; Ismail Petrus (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. CPD program mandated by the government becomes a means to improve teachers’ as well as students’ quality. CPD consists of self-development, scientific publication, and innovative work activities. The objectives of this study were to find out the types of CPD activities undertaken by the senior high school teachers of English in Palembang, the teachers' perception of CPD, and the challenges faced by the teachers in improving their professionalism through CPD program. This qualitative study employed a case study design. Questionnaires, interview, and documentation were used to collect the data. This study applied two questionnaires. The first questionnaire was used to obtain data about the types of teachers' CPD activities and its data were analyzed qualitatively. The second questionnaire in the form of a Likert scale was used to determine the teachers' perceptions of CPD and its data were analyzed descriptively. The data of the interview was analyzed using thematic analysis. Some copy of teachers’ CPD activities certificates were also used as proof of the teachers’ participation in the CPD program. The results indicated that the teachers had undertaken self-development and scientific publication activities. They had good perception of CPD and perceived it as activities to make them become more effective teachers. However, tight teaching schedules, family constraints, limited funds, and limited opportunities to participate in CPD activities become the challenges that the teachers had to face.Keywords: Continuing Professional Development (CPD), senior high school teachers, teachers of English